2011
DOI: 10.1093/nar/gkq1281
|View full text |Cite
|
Sign up to set email alerts
|

Insights into plant biomass conversion from the genome of the anaerobic thermophilic bacterium Caldicellulosiruptor bescii DSM 6725

Abstract: Caldicellulosiruptor bescii DSM 6725 utilizes various polysaccharides and grows efficiently on untreated high-lignin grasses and hardwood at an optimum temperature of ∼80°C. It is a promising anaerobic bacterium for studying high-temperature biomass conversion. Its genome contains 2666 protein-coding sequences organized into 1209 operons. Expression of 2196 genes (83%) was confirmed experimentally. At least 322 genes appear to have been obtained by lateral gene transfer (LGT). Putative functions were assigned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
175
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(183 citation statements)
references
References 69 publications
7
175
1
Order By: Relevance
“…The bacterium has been demonstrated to ferment crystalline cellulose, xylan, and insoluble extracts of the bioenergy feedstock switchgrass (12). In corroboration with this finding, within the genome of C. bescii is a large gene cluster in which nine genes were predicted to encode enzymes that either degrade cellulose or hemicellulose (12).…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…The bacterium has been demonstrated to ferment crystalline cellulose, xylan, and insoluble extracts of the bioenergy feedstock switchgrass (12). In corroboration with this finding, within the genome of C. bescii is a large gene cluster in which nine genes were predicted to encode enzymes that either degrade cellulose or hemicellulose (12).…”
mentioning
confidence: 66%
“…Recently, the complete genome sequencing of a thermophilic cellulose-and xylan-degrading bacterium (59), Caldicellulosiruptor bescii (previously classified as Anaerocellum thermophilum) (58), was accomplished (GenBank accession number CP001393) (12,30). The bacterium has been demonstrated to ferment crystalline cellulose, xylan, and insoluble extracts of the bioenergy feedstock switchgrass (12).…”
mentioning
confidence: 99%
“…S2) under the transcriptional control of the C. bescii S-layer protein (Cbes2303) promoter (P S-layer ). RNA profiling has shown that S-layer protein RNA is abundant throughout growth, suggesting that the promoter may be strong and constitutive (29). A rho-independent transcription terminator derived from a region immediately downstream of Cbes2303 was fused to the end of the adhE gene ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A number of genomes have been sequenced [57], and gene expression data was obtained during growth on cellulose [58]. The cellulase sets of Caldicellulosiruptor species are similar to the A. cellulolyticus set of cellulases.…”
Section: Caldicellulosiruptormentioning
confidence: 99%